PECULIARITIES OF PARTICIPATIONAL INTERACTION IN THE SYSTEM “PERSONS WITH DISABILITIES – SOCIETY” - Shustova1, Natalya; Luchenkova, Marina; Karina, Olga (Revista Inclusiones, 2021)
The article presents a theoretical review and empirical results highlighting the issue of the peculiarities of participational interaction in the system “persons with disabilities (PWD) – society.” The main contour of perception of PWD in modern society as well as the peculiarities of their subjective perception of the importance of participational interaction are characterized. The objective is to disclose the peculiarities of participational interaction of persons with disabilities in society on the basis of the authors’ typology. As a diagnostic tool the authors’ tool was used. The article presents the results of a theoretical analysis of modern Russian and foreign research which allowed us to single out the main predictors of participational process from the perspective of emotional, cognitive and behavioural aspects. The individual peculiarities of the manifestation of the development of the process of participation of persons with disabilities are presented. In the course of presentation of the empirical part of the research the typical models of participational interaction characterized of persons with disabilities are singled out. The means of realization of the set empirical objective is a cluster analysis.